Documentary heritage of “Lemkivshchyna” Society Museum in Archive of Historical Museum in Sanok: overview of art collection formation - Kozakevych Olena (Рукописна та книжкова спадщина України, 2023)

(untitled)
The goal of the research. Work purpose consists of the handwritten and printed materials analysis related to the “Lemkivshchyna” Society Museum activities, which are stored in the Archive of the Historical Museum in Sanok (Poland) as well as the study of the formative stages of the art museum collection (1931―1944) in the context of socio-cultural factors and its importance for Ukrainian cultural heritage. Methodology. In the research process, historical-comparative and historical-chronological methods were used to systematize archival documents, which helped to classify them according to thematic blocks. This facilitated to outline of the prerequisites for the creation of the museum and its structure, the main milestones of activity, the typology of the art collection, cooperation with other institutions, etc. Scientific novelty. The comprehensive analysis of the “Lemkivshchyna” archive (correspondence, reports, inventory books, reviews in periodicals, etc.), which is stored in the Historical Museum in Sanok was carried out. Special attention is given to features of exhibits acquisition and the art collection formation, its uniqueness, and significance for the Ukrainian cultural environment in the historical dimension. It was revealed that the objects were added to the collection thanks to the collecting activities of the museum staff, in particular, the director Lev Gets, in cooperation with representatives of the Lemko`s communities. The process was determined by the urgent need to preserve local material culture. Conclusions. The “Lemkivshchyna” Society Archive materials are almost unknown in Ukrainian humanitarian studies. It is necessary to publish original, uninterpreted documents, which are an important source for studying the activities of Ukrainian museums during the 1920s and early 1940s. First of all, these are factual sources that allow us to characterize the activities of the museum as objectively as possible and to analyze its artwork collection. In particular, the archive makes it possible to partially trace the subsequent history of the collection after the liquidation of the “Lemkivshchyna” museum, which was partly succeeded by the Historical Museum in Sanok.